2020
DOI: 10.23960/jbm.v16i3.126
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Gaya Kepemimpinan Transformasional dan Budaya Organisasi terhadap Kinerja dan Kepuasan Kerja sebagai variabel intervening

Abstract: The purpose of this research is to investigate the effects of transformational leadership style and corporate culture on job satisfaction as a variable intervening to enhance employee performance. The approach used in this study is a quantitative approach to data collection using questionnaires. The study was conducted at PT. Mahakam Berlian Samjaya the sample size is about 139 employees, using the Structural Equation Modelling (SEM). The results show that transformational leadership and organizational culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…Job satisfaction has an influence on employee performance. This is shown by several previous research results, including research conducted by Haryadi & Wahyudi (2020), Baskoro (2022), andFadzillah (2021). The results of their research found that job satisfaction has a positive and significant effect on employee performance.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…Job satisfaction has an influence on employee performance. This is shown by several previous research results, including research conducted by Haryadi & Wahyudi (2020), Baskoro (2022), andFadzillah (2021). The results of their research found that job satisfaction has a positive and significant effect on employee performance.…”
Section: Introductionmentioning
confidence: 61%
“…Recreation (Sunyoto, 2018). Kreitner and Kinicki (in Wibowo, 2016: 417) It was concluded that job satisfaction is a persons view of the results of the work he does and of the feedback given by the company on his work Based on some of the empirical research results above, the research hypothesis is stated as follows: H1 : The Higher the organizational Culture, the Higher the Job Satisfaction Haryadi & Wahyudi (2020) and Baskoro (2022) in the results of the study said that organizational culture has a significant effect on job satisfaction. The results of Suryajinggas research (2017) state that there is a positive and significant influence of organizational culture on job satisfaction.…”
Section: Job Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was discovered that distributive justice was a less significant predictor of job satisfaction than the impact of procedural justice [19]. The research revealed that employee performance is influenced by job satisfaction [30][31][32]. The results of research on full-time employees and a supervisor show that job satisfaction affects employee performance [33].…”
Section: The Impact Of Organizational Justice On Job Performance Medi...mentioning
confidence: 99%